Diagnosis of Multiple Organ Dysfunction in Neonates with Hypoxic–Ischemic Encephalopathy: Vasoactive Inotropic Score, Renal Score, Fibrosis-5 Index and Lactate/Albumin Ratio - Başak Kaya; Hasan Akduman; Dilek Dilli; Nilden Ünsal; Nurdan Dinlen Fettah; Ayşegül Zenciroğlu (Diagnostics)
Background: Vasoactive inotrope score, renal score, fibrosis-5 index, and lactate-albumin ratio have not been investigated before in determining multiple organ dysfunctions accompanying infants with hypoxic–ischemic encephalopathy (HIE) in neonatal intensive care units (NICUs). The aim of this study was to determine whether multiple organ dysfunctions that may accompany HIE in infants are correlated with vasoactive inotrope score (VIS), renal score (RS), fibrosis-5 index (FIB-5), and lactate-albumin ratio (LAR), and whether these parameters can predict morbidity and mortality. Methods: This is a retrospective study, and 106 newborns diagnosed with HIE and treated with hypothermia were included in the study. Vasoactive inotrope score for cardiac dysfunction, renal score for renal dysfunction, fibrosis-5 index, and lactate/albumin ratio for hepatic dysfunction were evaluated. Results: We found that the vasoactive inotrope score, renal score, fibrosis-5 index, and lactate-albumin ratio values of infants diagnosed with HIE are associated with cardiac, renal, and hepatic dysfunction. These values, calculated on the 2nd postnatal day, are particularly linked to prolonged hospital stay and mortality, which are key prognostic factors. Conclusions: Our study is the first to combine vasoactive inotrope score, renal score, fibrosis-5 index, and lactate-albumin ratio parameters in determining organ dysfunction in newborns with hypoxic–ischemic encephalopathy and to reveal their prognostic and mortality prediction values. Therefore, although it offers new perspectives, new studies are needed.